THE ROLE OF LPPL RADIO SWARA PERINTIS SUKABUMI IN TACKLING THE SPREAD HOAX THROUGH EFFORTS TO IMPROVE COMMUNITY LITERACY - Umban Adi Jaya; Cucu Hodijah; Siti Ashfiasari (Sekolah Tinggi Pariwisata Mataram, 2022)
Efforts to increase literacy are needed to combat hoaxes, one of which is by providing education to prevent hoaxes through radio media. LPPL Radio Swara Perintis Sukabumi is a broadcasting institution under the auspices of Dinas Komunikasi dan Informatika (Diskominfo) Kota Sukabumi. The purpose of this study is to understand the efforts of Diskominfo Kota Sukabumi in tackling hoaxes through LPPL, to understand how the role of LPPL in meeting information needs and increasing public literacy power as an effort to overcome the spread of hoaxes in Sukabumi City, and to find out the community's evaluation of the role of LPPL. This study uses qualitative methods, with data collection methods through field observations, interviews, and documentation. The results of the study illustrate that Diskominfo Kota Sukabumi and LPPL cooperate in dealing with hoaxes through various joint programs. In meeting the information needs in Sukabumi City as an effort to overcome hoaxes, LPPL comes with a variety of informative and educational broadcast programs and pays attention to the planning process to broadcasting that focuses on truth and accuracy. LPPL Radio Swara Perintis Sukabumi is also considered to have carried out its role in improving community media literacy well.